Answer:
1. sin a sin b = (1 / 2)[cos(a – b) – cos(a + b)]
Calculation:
Taking L.H.S. of above equation
(1 / 2)[cos(a – b) – cos(a + b)]
= (1 / 2) [ (cos a cos b + sin a sin b) - (cos a cos b - sin a sin b)]
{∵ cos(a – b) = cos a cos b + sin a sin b & cos(a + b) = cos a cos b - sin a sin b}
= (1 / 2) [ cos a cos b + sin a sin b - cos a cos b + sin a sin b]
= (1 / 2) [2 sin a sin b]
= sin a sin b
2. sin((π / 2) – x) = cos x
Calculation:
sin((π / 2) – x) = sin (π / 2) cos x - cos (π / 2) sin x
{∵sin(a - b) = sin a cos b - cos b sin a
& sin (π / 2) = 1 & cos (π / 2) = 0}
= 1 × cos x - 0 × sin x
= cos x